2006
DOI: 10.4315/0362-028x-69.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Effect of a Triclosan-Containing Floor Used in the Food Industry

Abstract: Antibacterial surfaces are increasingly used in the food industry. In the present study, the antibacterial effect of a triclosan-containing industrial floor was assessed. A poultry processing plant, which had a floor that contained triclosan, was visited, and the floor was sampled for bacteria. A high bacterial diversity was found on the floor. Testing showed that bacteria isolated from the floor showed a sensitivity to triclosan that covered a range of MICs from 0.07 to >40 ppm. Staphylococci were the most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
1
29
1
1
Order By: Relevance
“…The bacterial genera dominating in the abattoir after cleaning and disinfection were Aerococcus, Acinetobacter, Pseudomonas, Staphylococcus and Serratia. Several studies have reported the latter four genera to be common in the production environment of many types of food [9][10][11][12][13][14][15]. Aerococcus has been found in fish [12] and pastry production environments [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial genera dominating in the abattoir after cleaning and disinfection were Aerococcus, Acinetobacter, Pseudomonas, Staphylococcus and Serratia. Several studies have reported the latter four genera to be common in the production environment of many types of food [9][10][11][12][13][14][15]. Aerococcus has been found in fish [12] and pastry production environments [10].…”
Section: Discussionmentioning
confidence: 99%
“…In another study Pseudomonas and Staphylococcus dominated on the floor in a ground meat processing facility [10]. A comparison of qualitative determination of bacteria from different types of food production environments revealed that Pseudomonas, Staphylococcus, Acinetobacter, Bacillus, lactic acid bacteria and coryneforms commonly dominated [9][10][11][12][13][14][15]. The role of the commensal bacterial flora on food safety is not completely understood, but it may be involved in food spoilage, and affect pathogenic bacteria present in the food producing environment [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Various antimicrobial chemical agents that efficiently inactivate bacteria, known as biocides, are regularly used today to prevent bacterial contamination, especially in the food industry and in the home (Langsrud et al, 2004;Møretrø et al, 2006). In comparison with antibiotic resistance, bacterial resistance to biocides has only been described more recently, and has been less studied overall.…”
Section: Introductionmentioning
confidence: 99%
“…Processing, handling, and preparation of food may lead to cross-contamination of food and uncontaminated surface areas of the food chain with pathogens from contaminated surfaces (8). Though most processing plants ensure and maintain good manufacturing practices with elaborated sanitary operations, persisting microorganisms may survive well after cleaning and disinfection procedures (1,9,(12)(13)(14), possibly in the form of biofilms (11). A review of the underlying problems caused by biofilms in the food industry was presented by Carpentier and Cerf (4).…”
mentioning
confidence: 99%